An Investigation into the Modern Trends in Islāmic Da’wah (Preaching) in Yorubaland - Ismaila Boladale Lawal (Indonesian Journal for Islamic Studies, 2026)
Background: In Yorubaland, Nigeria, Islamic da’wah (preaching) traditions have changed dramatically due to the development of electronic and digital technologies. Traditional itinerant preaching has given way to technology-mediated methods. Although these developments have increased da’wah's reach, they have also brought forth new potential and difficulties that need for empirical research.Objective: By identifying modern da’wah techniques, assessing their effects on Yoruba Muslims, and analyzing the difficulties involved in their application, this study investigates the current developments in Islamic da’wah in Yorubaland.Method: A mixed-methods study design was used. In addition to non-participant observation, standardized questionnaires were used to gather quantitative data from 300 respondents chosen from the six states of Southwestern Nigeria. Descriptive statistics, such as percentages and frequencies, were used to analyze the data.Results: The results show that the most popular contemporary da’wah techniques include public address systems, radio, television, audio-visual media, and social media platforms. According to respondents, these strategies have improved religious knowledge (79.3%), increased youth participation (83.7%), and broadened the reach of Islamic teachings (82.3%). The absence of social media censorship (87.0%), the rise of unqualified self-styled preachers (86.0%), the careless use of public address systems (80.7%), and the propagation of hate speech (79.0%) are significant obstacles, nevertheless.Conclusion: In Yorubaland, modern technology has significantly increased the efficacy of Islamic da’wah, but it has also presented ethical and legal difficulties. To ensure authentic and long-lasting da’wah practices, it is imperative to adopt a code of conduct for preachers, strengthen institutional monitoring, and improve ICT proficiency among Islamic scholars.